Short Communication: Seed germination of twelve Indonesian begonias for conservation - MUHAMMAD EFENDI; AISYAH HANDAYANI; INTANI QUARTA LAILATY (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Efendi M, Handayani A, Lailaty IQ. 2019. Short Communication: Seed germination of twelve Indonesian begonias for conservation. Biodiversitas 20: 1192-1197. Knowledge of seed quality is essential when seeds are stored for the long term. A preliminary study on Begonia seed conservation was conducted, to characterize morphology and germination testing on native Begonia from Indonesia. As many as 12 species of Indonesian Begonia were observed for the characteristics of fruit and seeds. Later, we tested the level of seed viability at different levels of fruit maturity. The experimental design used a Completely Randomized Design (CRD) with two factors. Data analysis was performed using the Statistical Tool for Agricultural Research (STAR) program and further testing the Duncan Multiple Range Test (DMRT) at a 5% significance level. Generally, all seeds were barrel-like in shape, the smallest size in B. muricata (252.42 µm length), and the largest size in B. areolata (up to 451.42µm length, while the operculum 28.48 µm-104.9 µm length). Most Begonia seeds start germinating in the second and third weeks after sowing. B. scottii, and B. verecunda, as well as B. longifolia, showed germination in the second week, while other species tended not to be simultaneous. Dry seed germination was higher than seed wet for eight weeks. B. longifolia and B. scottii had the highest germination in wet seed treatment: while in the dry seed treatment, the highest germination was showed by B. areolata and B. muricata.